2023
DOI: 10.1111/nph.18673
|View full text |Cite
|
Sign up to set email alerts
|

Differential responses and mechanistic controls of soil phosphorus transformation in Eucalyptus plantations with N fertilization and introduced N2‐fixing tree species

Abstract: Summary Introducing N2‐fixing tree species into Eucalyptus plantations could replace nitrogen (N) fertilization to maintain high levels of N consumption and productivity. However, N enrichment may exacerbate phosphorus (P) limitation as Eucalyptus robusta Smith is extensively planted in P‐poor tropical and subtropical soils. We conducted a field experiment in a pure plantation of Eucalyptus urophylla × grandis to investigate the impacts of N fertilization and introduced an N2‐fixing tree of Dalbergia odorife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 75 publications
1
3
0
Order By: Relevance
“…By contrast, N addition decreased soil available Pi in both tropical and subtropical areas. In agreement, several new studies also reported that acid addition-induced pH reduction increased the occluded P fractions and decreased the labile P fraction in tropical soil (Hu et al, 2022;Yao et al, 2023). The likely explanation for this pattern is that soil acidification accelerates the solubility of minerals and also results in enrichment of highly charged exchangeable cations in strongly weathered tropical soils (X. M. Wang et al, 2013), thus enhancing the binding of dissolved Pi to their surfaces.…”
Section: Different Response Of Soil P Fractions To N and P Fertilizationsupporting
confidence: 75%
“…By contrast, N addition decreased soil available Pi in both tropical and subtropical areas. In agreement, several new studies also reported that acid addition-induced pH reduction increased the occluded P fractions and decreased the labile P fraction in tropical soil (Hu et al, 2022;Yao et al, 2023). The likely explanation for this pattern is that soil acidification accelerates the solubility of minerals and also results in enrichment of highly charged exchangeable cations in strongly weathered tropical soils (X. M. Wang et al, 2013), thus enhancing the binding of dissolved Pi to their surfaces.…”
Section: Different Response Of Soil P Fractions To N and P Fertilizationsupporting
confidence: 75%
“…The study area was situated along the southern edge of the south subtropical zone (Figure 1), bordering the northern tropics, and is characterized by a south subtropical monsoon climate [32]. It spans from 21 C as the warmest month.…”
Section: Overview Of the Experimental Site And Experimental Materialsmentioning
confidence: 99%
“…(Figure 1), bordering the northern tropics, and is characterized by a south subtropical monsoon climate [32]. It spans from 21°57′47″ N to 22°19′27″ N and from 106°39′50″ E to 106°59′30″ E. The average annual temperature is 21.5 °C, with January averaging 13.5 °C as the coldest month and July averaging 27.6 °C as the warmest month.…”
Section: Overview Of the Experimental Site And Experimental Materialsmentioning
confidence: 99%
“…A detailed investigation of P dynamics and bioavailability requires the separation and identification of different forms of P in soils [12]. Sequential fractionation is one of the most commonly used methods to study soil P dynamics owing to its advantages of low operating cost, small amount of samples needed, and practicality [13,14]. The P fractionation procedure of Hedley et al [15] and its modification by Tiessen and Moir [16] are the most commonly used [17][18][19].…”
Section: Introductionmentioning
confidence: 99%